Mediamorphosis understanding new media - Fidler, Roger F.; Sage eBooks (Thousand Oaks, Calif. ; London : Pine Forge, 1997)
Demystifies emerging media technologies and explains their potential influences on popular forms of mainstream media, such as newspapers, magazines, television, and radio, in the context of transformations in human communication since the emergence of written language. Discusses aspects including domains of communication media and the role of spoke.
Specialized.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Mass media -- History; Mass media -- Technological innovations; Mass media -- Forecasting; Electronic books